2018
DOI: 10.1371/journal.pone.0202603
|View full text |Cite
|
Sign up to set email alerts
|

Stillbirth in the African Great Lakes region: A pooled analysis of Demographic and Health Surveys

Abstract: BackgroundThe aim of this study was to estimate the rate and predisposing factors associated with stillbirth in the African Great Lakes region (Burundi, Congo Democratic Republic, Kenya, Rwanda, Tanzania and Uganda).Methods and findingsCross-sectional data from the most recent Demographic and Health Surveys (DHS) of countries in the African Great Lakes region were used in this study. DHS from Congo Democratic Republic was not included in the analyses because data was not collected for stillbirth in the country… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 31 publications
(25 reference statements)
3
23
1
Order By: Relevance
“…The association between lower socioeconomic status and higher stillbirth in this review is in agreement with previous studies conducted in other developing countries [ 44 , 45 ]. In addition, this review found a significant association between stillbirth and lower maternal education in Nepal, India, and Bangladesh; consistent with the Demographic and Health Survey in the African Great Lakes region [ 46 ]. However, studies conducted in Pakistan have found no significant association between stillbirth and maternal education [ 22 , 29 ].…”
Section: Discussionsupporting
confidence: 80%
“…The association between lower socioeconomic status and higher stillbirth in this review is in agreement with previous studies conducted in other developing countries [ 44 , 45 ]. In addition, this review found a significant association between stillbirth and lower maternal education in Nepal, India, and Bangladesh; consistent with the Demographic and Health Survey in the African Great Lakes region [ 46 ]. However, studies conducted in Pakistan have found no significant association between stillbirth and maternal education [ 22 , 29 ].…”
Section: Discussionsupporting
confidence: 80%
“…An increase in the composition of urban resident women over the survey showed a significant effect on the decrease in stillbirth. This finding is consistent within South Africa [34], African Great lake Regions [35], Nigeria [20], Northern Ghana [23] and Ethiopia [24]. This could be due to the increase in urbanization in Ethiopia over time [36] and increased urbanization has significant role in improving access to maternal health service especially emergency obstetric cases can be managed since they are near to the health facilities, and had relatively improved awareness towards maternal health service utilization as compared to rural residents [37].…”
Section: Discussionsupporting
confidence: 72%
“…The stillbirth rate of 67.5 per 1000 deliveries obtained in this study was much higher than the rate of 25 per 1000 deliveries recognized for low income and middle-income countries (Saleem et al, 2018). This rate is also a far cry from the stillbirth rate of 12 per 1000 deliveries recommended by the United Nations' Every Newborn Action Plan, which has set this goal to be attained in 2030 by all countries (Akombi et al, 2018;Saleem et al, 2018). The stillbirth rate of this study in Uyo, South-east health zone of Nigeria is comparable to the rate of 74 per 1000 deliveries that was obtained in Enugu, South-east Nigeria, probably because both study centers in Nigeria belong to the same health zone.…”
Section: Discussioncontrasting
confidence: 57%
“…In the Enugu, South-east Nigerian study, the odds of an un-booked mother being delivered of a stillborn infant was 1.56, p = 0.04, whereas parity was not significantly associated with the odds of stillbirth occurring (Ezugwu et al, 2011). On the other hand, a community based survey of 3 East African countries found, low level of education, advanced maternal age, smoking and drinking, as well as non-availability of potable water as risk factors that predisposed mothers to have stillbirth in that study (Akombi et al, 2018). Notwithstanding the preponderance of stillbirths among mothers with those risk factors, these may have confounded with their socioeconomic circumstance, which could have undermined their ability to receive quality antenatal care.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation